46-3n=-26

Simple and best practice solution for 46-3n=-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 46-3n=-26 equation:


Simplifying
46 + -3n = -26

Solving
46 + -3n = -26

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-46' to each side of the equation.
46 + -46 + -3n = -26 + -46

Combine like terms: 46 + -46 = 0
0 + -3n = -26 + -46
-3n = -26 + -46

Combine like terms: -26 + -46 = -72
-3n = -72

Divide each side by '-3'.
n = 24

Simplifying
n = 24

See similar equations:

| 2x-3/8-x-2/6 | | 38k+7k=8(k+4) | | 8x^2+7x+6=0 | | 4x-w=vx+y | | 15=17x+5-5x | | 5+3c+4c= | | 14=9x+2-6 | | 1=3u-5 | | 16x^3+250=0 | | 1/2(2x-6)=4(1/4x-3/4) | | 28y+8=16 | | 6x+29=13-48 | | -7x+8+-4+-9= | | 20*log(x)=55 | | 2.00+1.50=54.5 | | -3(4v-9)+7v=4(v+6) | | 20log(x)=55 | | 2(12p+16)= | | 6=-4.1+r | | x+.06x=400 | | 268+3*g=654 | | -25.8=43v | | 268+3*g=900 | | h=15t-4.9t^2+2 | | c+4.3=-6.7 | | 5x+1=-5x-1 | | (Dy/dx)=3e^5 | | 5.6=f-64 | | 148-(56+j)=24 | | 12x-2.4.2x-1/8x.3x-4 | | 7y+-8y= | | 6.5h=39 |

Equations solver categories